Pengaruh Laba Bersih dan Arus Kas terhadap Dividen Tunai (Studi Kasus Pada Perusahaan Sektor Pertambangan Yang Terdaftar di Bursa Efek Indonesia Periode 2014-2019) - Ribka Natarmi; Liya Megawati (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2022)
Trade of war between the US and China has had a significant negative impact on the industry in Indonesia, one of which is the industrial sector mine. Not only the company but shareholders are also impacted such as the distribution of dividends is decreased because of declining profit and unstable cash flow of the company.This study aims to determine Net Profit, Cash Flow, and Cash Dividends with test and analyze how much influence Net Profit and Cash Flow have on Cash Dividends in Mining Sector Companies Listed on the IDX in 2014-2019. In this study, 48 mining companies entered the mining sector on the IDX. The method used in this study is purposive sampling, 7 companies are used as samples because they have met the sampling criteria. The analytical method used is descriptive analysis and verification analysis with a quantitative approach. Multiple linear regression analysis data, t-test, and F test. The results of this study show that net income affects cash dividends, cash flow has no significant effect on cash dividends, and simultaneously net income and cash flows have affected cash dividends.